Complex case discussion for Clinical Psychology Masterclass 2019 Ministry of Health - Abdul Khaiyom, Jamilah Hanum (2019)
Four complex cases were discussed and suggestions were provided. Case 1 was about young adult gentleman with Major Depressive Disorder, comorbidity with Asperger syndrome and borderline personality trait. Case 2 was on a teenage girl who suddenly regressed to a 'baby-like' stage in terms of speech and behaviors. Case 3 was on a child with selective mutism. Case 4 was about a child who was claimed by the mother to be sexually assaults by the father. The mother keep requesting the attending psychologist to provide report for Hadanah, eventhough the assessment is yet to complete.